Ganancia excesiva de peso gestacional y duración de la lactancia materna como factores riesgo de obesidad infantil - Cotera Orbegozo, Sarvia Ines (2020)
Obesity is an epidemic, and childhood obesity is the great public health problem of the 21st century whose prevalence is increasing alarmingly in developed countries; however, this has not become alien to our reality as a third world country, this chronic disease favors the early onset of chronic pathologies such as cardiovascular and endocrine diseases and maintains its prevalence in adulthood. OBJECTIVE: To determine if excessive weight gain during pregnancy and the duration of breastfeeding are factors that increase the risk of obesity in children under 5 years of age at Hospital Belén de Trujillo during the period from February to September 2020. METHODOLOGY: Observational, analytical, retrospective study of cases and controls. Review of medical records of children under 5 years of age seen during the period from February to September 2020 in outpatient pediatric clinics at Hospital Belén de Trujillo. The sample size would be 62 obese children (cases) and 124 children with normal weight (controls). IMPORTANCE: There is evidence in other areas of this association between excessive weight gain during pregnancy and the risk of obesity in the offspring and that the practice of breastfeeding could prevent the onset of obesity in the medium and long term, but there is no studies in our environment that relate excessive weight gain during pregnancy, the performance of SCI and its duration with the presence of obesity in children; therefore, understanding the appearance of obesity in childhood can offer opportunities to improve health at all ages and even in the mother during her pregnancy and lactation period, which is why it is necessary to establish preventive promotional actions in the mother and child. if this relationship is established between gestational weight gain, the duration of breastfeeding and obesity in children under five years of age.